2003
DOI: 10.1300/j091v17n03_04
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Mycorrhization and Fertilization on Growth, Nutrition, and Water Relations of Sweet Birch

Abstract: Pisolithus tinctorius (Pers.) Coker & Couch was evaluated as an ectomycorrhizal associate of sweet birch (Betula lenta L.). Sand culture and mine soil growth media were employed, and three fertilization treatments were imposed by application of differing Hoagland's nutrient solution #2 concentrations. The high fertilization treatment suppressed mycorrhizal formation by P. tinctorius in both growth media, while the medium rather than the low treatment induced the most extensive colonization by this mycobiont. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Nursery practices must be fine-tuned to encourage colonisation by T. melanosporum, but also to improve vegetative quality of seedlings. However, in nursery fertilisation experiments a conflict between optimal seedling growth and EM colonisation has been reported for many EM fungi (Castellano & Molina 1989, Walker et al 2003, Diaz et al 2010. Two mechanisms have been suggested to explain this conflict: (i) the host reducing carbon supply to the fungus due to a greater carbon demand by growing shoots, or (ii) the fungus requiring most carbon received from the plant to assimilation of the greater N uptake (Wallander 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nursery practices must be fine-tuned to encourage colonisation by T. melanosporum, but also to improve vegetative quality of seedlings. However, in nursery fertilisation experiments a conflict between optimal seedling growth and EM colonisation has been reported for many EM fungi (Castellano & Molina 1989, Walker et al 2003, Diaz et al 2010. Two mechanisms have been suggested to explain this conflict: (i) the host reducing carbon supply to the fungus due to a greater carbon demand by growing shoots, or (ii) the fungus requiring most carbon received from the plant to assimilation of the greater N uptake (Wallander 1995).…”
Section: Discussionmentioning
confidence: 99%
“…However, Treseder (2004 showed that nitrogen (N) and phosphorus (P) fertilisations decrease mycorrhizal abundance in the field. In nursery experiments, high fertilisation levels have been found to inhibit the formation of ectomycorrhizas of many fungal species including T. melanosporum (Dupré et al 1982, Beckjord et al 1985, Walker et al 2003, Diaz et al 2010, although Castellano & Molina (1989) noticed that some species are much more tolerant and that fertilisation effect was dependent on the application system, fertiliser type, dose and form. On the other side, Quoreshi & Timmer (2000) and Rincon et al (2007) found fertiliser doses that increased growth of containerised conifer seedling without decreasing colonisation levels of inoculated fungi from various EM species.…”
Section: Introductionmentioning
confidence: 99%
“…There is much less synthesized information about EcMF effects on micronutrients (George et al 1994). It appears that effects on micronutrients may be contingent on both host and symbiont (e.g., Mitchell et al 1984Mitchell et al , 1990Dixon and Hiol-Hiol 1992;Walker et al 2003).…”
Section: Thelephora Terrestrismentioning
confidence: 99%
“…Janowska et al [35] observed that another growth regulator-BA-applied at 600 mg•dm −3 , stimulated the uptake of Mn and Zn in G. hybridus 'Black Velvet', whereas, at concentrations ranging from 100 to 600 mg•dm −3 , it stimulated the B uptake but inhibited the Cu uptake. Walker et al [37] observed a similar phenomenon in Betula lenta leaves. Janowska et al [26] found that mycorrization only affected the Mn content in Zantedeschia albomaculata leaves but had no effect on the content of Na and other microelements.…”
Section: Content Of Microelementsmentioning
confidence: 71%